Archaeological Sites as a Component of the Modern Religious Worldview of the Southern Ural Population (Based on the Example of the Akhunovo Megalithic Complex) - Tuzbekov, Ainur I.; Akhatov, Albert T. (Studia mythologica Slavica, 2020)
The present research examines the problem of the formation of new sacred sites around one of the most well-known archaeological complexes of the Bronze Age in the Southern Urals. To do so, the author applied the results of field research done of his own at the Akhunovo cromlech and analysed scientific literature and internet resources. Proceeding from the received data, the author traced the process of formation of sacred insight of the monument, determined the main reasons and participants of the sacralisation process and established probable negative outcomes of this phenomenon.